Impact of The Pandemic on The Logistics of Dairy Products - Valentina SHARAPOVA; Natalia SHARAPOVA; Yuri SHARAPOV (Communications of International Proceedings, 2020)
The most important food security industry is dairy. Recently, there has been an increase in the production of dairy products due to an increase in milk yield per cow. Despite the growth in production, the indicators approved in the Food Security Doctrine have not yet been achieved. Milk and dairy products produced by Russian agricultural producers are not enough to meet the needs of the population. To reduce the surplus, the state purchases dairy products from foreign countries, despite the high level of costs associated with logistics and product sales. Logistics costs can be reduced by optimizing milk delivery costs and reducing customs duties. Due to the decrease in the purchasing power of the population, the demand for dairy products is also decreasing. Despite the negative impact of the pandemic on the economic performance of the dairy industry due to the difficult situation of small businesses, the industry remains attractive for investors. The methodological basis was the works of both domestic and foreign scientists in the field of food security, logistics of dairy products and government regulation of the industry. The information base was the data of state statistics. Use the word “Abstract” as the title for the abstract section.   The abstract should be no more than 250 words. It should capture research motivation, research Design/methodology, and main findings and implications.  The abstract should provide an excellent summary of the paper.
Keywords: Dairy industry; logistics; import of raw milk; food security.